2006
DOI: 10.1002/ptr.1893
|View full text |Cite
|
Sign up to set email alerts
|

Effect on capillary permeability in rabbits of iridoids from Buddleia scordioides

Abstract: The methanol soluble fraction of the leaves of Buddleia scordioides after column chromatography resulted in the isolation of two known iridoid glucosides, catalpol and methylcatalpol. The structures were elucidated by extensive 1D-2D-NMR spectroscopy. The structure of methylcatalpol was confirmed by single-crystal x-ray diffraction. These compounds showed protective activity against increased (both chloroform and histamine) skin vascular permeability in rabbits. The protective effect was measured as the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
1
7
0
Order By: Relevance
“…The efficacy, tolerability and safety of HR has also been proven (33)(34)(35)(36)(37)(38)(39)(40)42) and confirmed in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The efficacy, tolerability and safety of HR has also been proven (33)(34)(35)(36)(37)(38)(39)(40)42) and confirmed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…HR is very effective in treating edema and therefore has a special indication in diabetic patients with CVI. Recent studies (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) have also shown the efficacy of HR in CVI for controlling plasma free radicals (9).…”
Section: Discussionmentioning
confidence: 98%
“…7-10 It can treat a variety of ailments such as diabetes, constipation, urinary tract problems, anemia, dizziness, and regulate menstrual ow. 1,13,14 Acteoside, another main active compound of Rehmannia glutinosa Libosch, shows anti-inammatory and antioxidant potentials. 11 The main active principal is catalpol which is reported to make up 2.7-10.6% of the medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The methylcatalpol, {1a,1b,2,5a,6,6a-hexahydro-1a-(hydroxyl-methyl)-6-methoxy oxireno [4,5]cyclopenta [1,2c]pyran-2-yl-β-D-glucopyranoside}, which extracted from the leaves of Buddlejadavidii, is a compound belonging to the family of iridoid glycoside. It is a mono-O-methyl derivative of catalpol (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…). The hydrogen bonds O(5)-H(5)...O(6) and O(7)-H(7)...O(6) form two five-membered rings, respectively. Another six-member hydrogen-bonded ring is also formed through the N(1)-H(1)...O(2) hydrogen bond, with atoms C3, C8 and C9.…”
mentioning
confidence: 99%